Oral health of visually impaired and sighted children residing in institutions: A comparative cross-sectional study - Kavyashree Gururaj Hebbar; Girish Babu KL (Arbu Academic Publishing, 2022)
Aim: To evaluate the oral health status among Visually Impaired (VI) and sighted children residing in institutions. Methods: VI and sighted children aged 6 to 14 years and residing in the institutions participated. The data on the chronological age and the status of visual impairment of children were collected from the medical records available with the institutional authorities. Oral health-related quality of life (OHRQoL) was recorded using a questionnaire. The status of oral hygiene, dental caries, gingiva, and traumatic dental injury were assessed. Results: A total of 206 children participated (103 of VI and 103 sighted children). Among VI children, the prevalence of dental caries in primary and permanent dentition was 32% and 45%, respectively, which was higher than sighted children. The mean difference of DMFT between VI and sighted children was statistically significant but not deft. The mean value of oral hygiene status was 1.52±0.94 in VI children and 0.76±0.02 in sighted children. Twenty-seven percent, 44%, and 28% of VI children had moderate gingivitis, mild gingivitis, and normal gingiva. Elli's Class I and II fracture was seen in 12% and 9% of VI children, respectively. The quality of life due to oral health was compromised in VI children compared to sighted children. There was a strong correlation between assessed oral health parameters and the various domains of OHRQoL between VI and sighted children. Conclusions: The VI children had a significantly higher prevalence of dental caries, traumatic dental injuries and gingival inflammation with poor oral hygiene compared to sighted children. The poor oral health influenced the quality of life of VI children more than sighted children.